2020
DOI: 10.15575/ak.v7i1.6497
|View full text |Cite
|
Sign up to set email alerts
|

Penyiapan Arang Aktif Pelepah Kelapa Sawit sebagai Adsorben Asam Lemak Bebas dari CPO (Crude Palm Oil)

Abstract: Limbah pelepah sawit (LPS) dihasilkan secara periodik dari perkebunan kelapa sawit. Keberadaan LPS ini berpeluang digunakan sebagai bahan baku adsorben. LPS telah diubah menjadi arang aktif pelepah sawit (APS) melalui langkah karbonisasi pada temperatur 600oC selama waktu bervariasi (30, 60, dan 120 menit). APS yang diperoleh dilakukan analisis kadar air, abu dan zat menguap. APS juga dikarakterisasi dengan FTIR untuk menentukan gugus fungsi, keasaman permukaan dengan tirasi Bhoem serta SEM untuk mendeteksi mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…With increasing time, the number of vacant sites decreases, so the adsorption rate is slow. At one point, when the adsorption sites are depleted, there will be repulsion between the adsorbate on the surface of the adsorbent and the adsorbate for FFA [38]. Interestingly, we found that the addition of adsorbent of MS-POBA free template (4.12%) and MS-POBA with the template (4.68%) onto CPO resulted in the value of FFA having been considered to SNI standard.…”
Section: The Effect Of the Contact Timementioning
confidence: 91%
“…With increasing time, the number of vacant sites decreases, so the adsorption rate is slow. At one point, when the adsorption sites are depleted, there will be repulsion between the adsorbate on the surface of the adsorbent and the adsorbate for FFA [38]. Interestingly, we found that the addition of adsorbent of MS-POBA free template (4.12%) and MS-POBA with the template (4.68%) onto CPO resulted in the value of FFA having been considered to SNI standard.…”
Section: The Effect Of the Contact Timementioning
confidence: 91%
“…The palm fronds waste has been converted into palm frond charcoal (Charcoal Oil Palm Fronds, COPF) with a calcination temperature of 600°C and a variation of 30, 60, and 120 minutes. The most significant efficiency of free fatty acid adsorption in CPO at COPF 600 at 60 minutes of carbonization time was 77.81% [4]. Research by Melati et al [5] proves that activated carbon is effectively used as an adsorbent for solids, liquids, or gas.…”
Section: Introductionmentioning
confidence: 97%
“…The adsorption efficiency of Fe from peat water is still relatively low; therefore, it is required to discover other sources, such as oil palm fronds waste, that are simple to find and prepare, environmentally friendly, timeefficient in decreasing Fe, and cost-effective. From the explanation above, an adsorbent based on palm frond charcoal will be synthesized with carbonization temperature variations of 400, 500, and 600°C for 60 minutes based on Muhdarina et al [4] and applied to the adsorption of Fe (III) in peat water based on Harfinda [7]. This research is expected to optimize local natural resources from oil palm frond biomass and to reduce Fe (III) levels from peat water.…”
Section: Introductionmentioning
confidence: 99%